Simplified Calculation of Maximum Conductor Tension at Two Stages of Their Movement During Short Circuit - I. I. Serguei; A. P. Androukevich; Е. G. Ponomarenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains formulae of the simplified calculation of maximum conductor tension at stages of their movement during short circuit. Assurance estimation of the simplified calculation is done on the basis of the experimental data and calculative experiment. Correction factors for higher accuracy of the simplified calculation are proposed in the paper.